Strawberry dietary fiber functionalized with phenolic antioxidants from olives. Interactions between polysaccharides and phenolic compounds. (15th May 2019) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Fernández-Prior, África; Vioque, Blanca; Fernández-Bolaños, Juan
Highlights: Interaction of olive phenols HT/DHPG with strawberry cell wall occurs with drying. Phenol-polysaccharide interactions occur through covalent and non-covalent bonds as suggested by MALDI TOF-TOF. Phenol-strawberry dietary fiber complex antioxidant activity. Reduction of polysaccharide size enhanced the complex's antioxidant activity. The complex combines the functional properties of dietary fiber and antioxidant. Abstract: The interaction of strawberry cell wall with hydroxytyrosol (HT) and 3, 4-dihydroxyphenylglycol (DHPG), two potent phenolic antioxidants naturally found in olive fruit with important biological properties, was investigated. The interaction occurred with drying and seemed to be more complex, strong and irreversible than a simple association. MALDI TOF-TOF analysis suggested covalent (ester bond) and non-covalent (strong hydrogen-bonding, mostly) interactions. The oxygen radical absorbance capacity (ORAC) assay confirmed that the phenols maintained partially their antioxidant activity after binding to the soluble dietary fraction. This soluble dietary fiber was obtained following digestion simulated in vitro with gastric and intestinal fluids. Although the antioxidant activity of HT and DHPG was affected by the dietary fiber interaction, this activity was restored when polysaccharide size was reduced by enzymatic treatment, suggesting that a similar process could occur in the colon. Thus, the use of this novel antioxidant-enriched soluble dietary fiber as a functional food ingredient could potentially promote intestinal health.